Effect of Different Error Correction Algorithms on Video Quality over Heterogeneous Networks - Osamah, I. Khalaf (IOP Publishing, 2015)

(untitled)
Video transferring over Heterogeneous Networks has been considered as one of the most significant subject to study because this process involve in a great number of new applications,which contributed in increasing the number of the users for this type of network.Transferring video in this type of network may suffer from many problems such as connection failures, weakness in the network layer, fading, network traffic overload, storage capacity, and so on. This study involves analyzing video transmission over heterogeneous using Network Simulation-NS2,the main errors which have occurred during video transferring, the types of video transmission techniques error correction methods,and various performance parameters such as the packet delivery ratio, throughput, normalized overhead control, and peak signal to noise ratio. The effect on the quality of the delivered video are calculated, and the results show that the quality of video transmitted over heterogeneous networks has improved using the proposed algorithm.